Estrogenic modulation of female thermoregulatory behavior in a cold environment - Yuki Uchida; Kei Nagashima; Shuri Marui (Japanese Society of Physical Fitness and Sports Medicine, 2016)
Thermoregulation is categorized as either autonomic (i.e., sweating, shivering) or behavioral (i.e., wearing clothes, usage of air conditioner) thermoregulation. Compared to autonomic thermoregulation, the neural pathway of behavioral thermoregulation in cold environments remains unclear. A decrease in ambient temperature is perceived through thermoreceptors for detecting cold, including transient receptor potential (TRP) channels, such as TRPM8 and TRPA1, which are expressed in the sensory nerve endings of the skin. From these receptors, nerves connect to the dorsal root ganglion and dorsal horn in the spinal cord, and arrive at the lateral parabrachial nucleus in the pons, which is the same neural pathway that is used for autonomic thermoregulation. Following this, an unknown neural pathway induces thermoregulatory behavior, such as cold-escape behavior. Both young and climacteric women complain of an unpleasant thermal comfort, which is attributed to "hie-sho" (chill or poor blood circulation). The altered thermal sensation and comfort by an absence or a fluctuation of estrogen (E2) may modulate behavioral thermoregulation in females. This effect is unknown in women. However, in ovariectomized rats, E2 facilitated thermoregulatory behavior in the cold, as evaluated by an operant system and tail-hiding behavior, a possible new behavioral indicator that we reported. E2 decreased neural activity in the insular cortex, as assessed by cFos immunohistochemistry, while tail-hiding behavior increased in colder temperatures. We speculate that the suppression of neural activity in the insular cortex by E2 may be related to behavioral thermoregulation in a cold environment. Therefore, it is necessary to clarify the effects of E2 on TRPM8 and TRPA1 channels, and the neural pathway of behavioral thermoregulation.